Face recognition system using DCT features implemented on DSP processor - Raja Abdullah Raja Ahmad (School of Computer and Communication Engineering, Universiti Malaysia Perlis, 2015)
Face recognition is a challenge because the faces always change due to facial expression, direction, light, and scale. Furthermore, it needs good computing techniques for recognition in order to reduce the system's complexity. Our approach focuses on the local feature extraction in the frequency domain. DCT was proposed as the feature extraction algorithm for face recognition, which captures the important features in the face image and at the same time reduces the feature space. PCA then performs the feature reduction of the extracted image and produces a small size of feature vector. The propose method can reduce data dimension in feature space.